Essential Genes and MiRNA–mRNA Network Contributing to the Pathogenesis of Idiopathic Pulmonary Arterial Hypertension - Hao, Shengyu; Jiang, Pan; Xie, Liang; Xiang, Guiling; Liu, Zilong; Hu, Weiping; Wu, Qinhan; Jiang, Liyan; Xiao, Yi; Li, Shanqun (Frontiers in Cardiovascular Medicine, 2021)
Background: Idiopathic pulmonary arterial hypertension (IPAH) is a life-threatening disease. Owing to its high fatality rate and narrow therapeutic options, identification of the pathogenic mechanisms of IPAH is becoming increasingly important. Methods: In our research, we utilized the robust rank aggregation (RRA) method to integrate four eligible pulmonary arterial hypertension (PAH) microarray datasets and identified the significant differentially expressed genes (DEGs) between IPAH and normal samples. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were performed to analyze their functions. The interaction network of protein–protein interaction (PPI) was constructed to explore the correlation between these DEGs. The functional modules and hub genes were further identified by the weighted gene coexpression network analysis (WGCNA). Moreover, a miRNA microarray dataset was involved and analyzed to filter differentially expressed miRNAs (DE-miRNAs). Potential target genes of screened DE-miRNAs were predicted and merged with DEGs to explore a miRNA–mRNA network in IPAH. Some hub genes were selected and validated by RT-PCR in lung tissues from the PAH animal model. Results: A total of 260 DEGs, consisting of 183 upregulated and 77 downregulated significant DEGs, were identified, and some of those genes were novel. Their molecular roles in the etiology of IPAH remained vague. The most crucial functional module involved in IPAH is mainly enriched in biological processes, including leukocyte migration, cell chemotaxis, and myeloid leukocyte migration. Construction and analysis of the PPI network showed that CXCL10, CXCL9, CCR1, CX3CR1, CX3CL1, CXCR2, CXCR1, PF4, CCL4L1, and ADORA3 were recognized as top 10 hub genes with high connectivity degrees. WGCNA further identified five main functional modules involved in the pathogenesis of IPAH. Twelve upregulated DE-miRNAs and nine downregulated DE-miRNAs were identified. Among them, four downregulated DEGs and eight upregulated DEGs were supposed to be negatively regulated by three upregulated DE-miRNAs and three downregulated DE-miRNAs, respectively. Conclusions: This study identifies some key and functional coexpression modules involved in IPAH, as well as a potential IPAH-related miRNA–mRNA regulated network. It provides deepening insights into the molecular mechanisms and provides vital clues in seeking novel therapeutic targets for IPAH.